Humor in Advertising - Koneska, Prof. Dr. Ljiljana; Teofilovska, Jasna; Dimitrieska, Savica (European Journal of Economics and Business Studies, 2017)
Creating good advertising message is very important segment in the promotion of a company. Companies use different advertising appeals to encourage consumers to buy products and services. Humor is one of those advertising appeals. The first task of humor is to attract the consumers’ attention through an interesting, entertaining, provocative, unexpected, sudden and memorable message. Humor aims to help consumers in decision-buying process. However, humor can cause negative side effects if it insults, is used in inappropriate manner or is too excessive. Recent studies show that companies are successful if they use “intelligent” humor that is related to the products’ nature and function. The purpose of this paper is to present the attitude of consumers towards the humorous advertisements and to explore the concept and usage of humor in advertising to find out its impact on consumer’s purchase decision.
Keywords: humor, advertisement, appeals, promotion"People do not buy from clowns." Claude Hopkins 1923"I have reason to believe that... humor can now sell." David Ogilvy 1982